2021
DOI: 10.1111/1556-4029.14869
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community succession on submerged vertebrate carcasses in a tidal river habitat: Implications for aquatic forensic investigations

Abstract: Death investigations in aquatic ecosystems are challenging due to abiotic and biotic factors that may influence the estimation of a postmortem submersion interval (PMSI).In this study, we examined bacterial changes throughout the decomposition process on porcine carcasses submerged in a tidal-influenced river and identified predictors of epinecrotic community succession. Fetal porcine (Sus scrofa) carcasses (N = 6) were submerged with epinecrotic samples collected every 3 days (6 collections) over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 71 publications
(174 reference statements)
1
10
0
Order By: Relevance
“…Despite differences among study location and design, the predominate phyla identified here were similar among other decomposition studies. Firmicutes, Bacteroidetes, and Proteobacteria were predominate taxa in this study, but were also prevalent in terrestrial decomposition [7,50,53], other aquatic decomposition [9,10,20,21,61], and bone postmortem microbiomes [16,17]. Basidiomycota and Mucoromycota were predominate taxa in terrestrial [8,18,19,55,57] and aquatic decomposition and identified as important taxa in our study as well [11].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Despite differences among study location and design, the predominate phyla identified here were similar among other decomposition studies. Firmicutes, Bacteroidetes, and Proteobacteria were predominate taxa in this study, but were also prevalent in terrestrial decomposition [7,50,53], other aquatic decomposition [9,10,20,21,61], and bone postmortem microbiomes [16,17]. Basidiomycota and Mucoromycota were predominate taxa in terrestrial [8,18,19,55,57] and aquatic decomposition and identified as important taxa in our study as well [11].…”
Section: Discussionsupporting
confidence: 60%
“…For aquatic decomposition, many previous studies used nonhuman surrogates. These include tiles for biofilm formation [60], swine remains [9,11,20,21,61],…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations